Composite dressing with photothermal synergistic antibacterial repair, preparation method and application

By using composite dressings prepared with materials such as polycaprolactone, bioactive glass, tea polyphenols and black phosphorus, the problem of repeated infiltration and infection of traditional dressings in wound treatment is solved, and the effect of photothermal synergistic antibacterial repair and promoting wound healing is achieved.

CN119113177BActive Publication Date: 2025-03-28GUIZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411255510.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-28
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

When treating wounds, traditional wet dressings can easily lead to repeated infiltration of fluid, increasing the risk of infection, and at the same time it is difficult to effectively block bacteria and promote tissue repair.

Method used

A composite dressing consisting of polycaprolactone (PCL), bioactive glass (BG), tea polyphenols (TP) and black phosphorus (BP) was used to prepare nanofiber membranes with Janus structure through electrospinning technology to achieve photothermal synergistic antibacterial repair.

Benefits of technology

This dressing has excellent biocompatibility and significant photothermal antibacterial properties, can effectively promote wound healing, and has multiple functions composite dressings, with great potential for promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113177B_ABST
    Figure CN119113177B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite dressing with photothermal synergistic antibacterial repair, a preparation method and an application. The composite dressing with photothermal synergistic antibacterial repair comprises an inner nanofiber membrane and an outer nanofiber membrane. The present invention also provides a method for preparing a composite dressing, comprising: adding polycaprolactone and magnesium-containing bioactive glass to an organic solvent to obtain a first mixed solution; adding polycaprolactone and tea polyphenols to an organic solvent to obtain a second mixed solution; electrospinning the first mixed solution to obtain an inner nanofiber membrane; electrospinning the second mixed solution onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane to obtain a composite dressing. The present invention also provides an application of a composite dressing with photothermal synergistic antibacterial repair as described in the present invention in the preparation of a wound repair drug. The present invention provides a wound dressing that has both photothermal antibacterial and tissue repair promoting properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a composite dressing with photothermal synergistic antibacterial repair, a preparation method and application thereof. Background Art

[0002] As the first line of defense of the human immune system, the skin plays a vital role. It is a protective barrier for our body, resisting the invasion of various harmful substances from the outside world. However, traditional wet dressings often encounter a problem when treating wounds, that is, the wound is easily infiltrated repeatedly by effusion. This repeated infiltration of effusion not only causes discomfort, but also provides a breeding ground for bacteria, thereby increasing the risk of infection. Therefore, there are two core issues that need to be solved in the research and development of wound dressings: one is how to effectively block pathogens and prevent wound infection; the other is how to have a good effect in promoting tissue repair and helping wounds heal faster. Only when these two conditions are met at the same time can an effective solution for wound care be truly provided. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a dressing with photothermal synergistic antibacterial and repairing properties, a preparation method and an application, so as to provide a wound dressing that has both photothermal antibacterial properties and promotes tissue repair.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A composite dressing with photothermal synergistic antibacterial repair, comprising an inner nanofiber membrane and an outer nanofiber membrane;

[0006] The inner nanofiber membrane comprises polycaprolactone (PCL) and bioactive glass (BG) containing magnesium;

[0007] The outer nanofiber membrane comprises polycaprolactone (PCL) and tea polyphenols (TP).

[0008] Preferably, the outer layer nanofiber membrane also comprises black phosphorus (BP).

[0009] Preferably, the mass percentage of the polycaprolactone (PCL) and the magnesium-containing bioactive glass (BG) is 94% to 98%: 2% to 6%.

[0010] Preferably, the mass percentages of the polycaprolactone (PCL) and tea polyphenols (TP) are 85% to 95%: 5% to 15%.

[0011] The present invention also provides a method for preparing the composite dressing with photothermal synergistic antibacterial repair as described in the present invention, comprising the following steps:

[0012] adding polycaprolactone (PCL) and bioactive glass (BG) containing magnesium into an organic solvent to obtain a first mixed solution;

[0013] adding polycaprolactone (PCL) and tea polyphenols (TP) into an organic solvent to obtain a second mixed solution;

[0014] Electrospinning the first mixed solution to obtain an inner nanofiber membrane;

[0015] The second mixed solution is electrospun onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane, thereby obtaining a composite dressing with photothermal synergistic antibacterial repair.

[0016] Preferably, the method for preparing the magnesium-containing bioactive glass comprises:

[0017] dissolving tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and magnesium nitrate hexahydrate in a nitric acid aqueous solution in sequence to obtain a sol solution;

[0018] The sol solution is sealed and allowed to stand to obtain a gel;

[0019] The gel is aged, dried and heat treated to obtain magnesium-containing bioactive glass.

[0020] Preferably, the molar ratio of tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and magnesium nitrate hexahydrate is 55-65:6-10:29-33:2-8.

[0021] Preferably, the molar ratio of tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and magnesium nitrate hexahydrate is 60:8:31:5.

[0022] Preferably, the concentration of nitric acid in the nitric acid aqueous solution is 0.18M to 0.22M.

[0023] Preferably, the concentration of nitric acid in the nitric acid aqueous solution is 0.2M.

[0024] Preferably, the sealed and standing temperature is 37° C., and the sealed and standing time is 3 days.

[0025] Preferably, the aging temperature is 70° C. and the aging time is 3 days.

[0026] Preferably, the drying temperature is 120° C. and the drying time is 2 days.

[0027] Preferably, the heat treatment temperature is 600° C., the heat treatment time is 3 h, the heating method of the heat treatment is programmed heating, and the heating rate of the programmed heating is 2° C. / min.

[0028] Preferably, the second mixed solution further comprises black phosphorus (BP);

[0029] The concentration of the black phosphorus (BP) in the second mixed solution is 150 μg / mL to 200 μg / mL.

[0030] Preferably, the process parameters of the electrospinning are: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0031] Preferably, the electrospinning is carried out under light-proof conditions.

[0032] Preferably, the organic solvent is a mixed solvent of dichloromethane and N,N-dimethylformamide;

[0033] The volume ratio of dichloromethane to N,N-dimethylformamide in the mixed solvent is 7:3;

[0034] Preferably, after forming the outer layer of nanofiber membrane on the inner layer of nanofiber membrane, the method further comprises: vacuum drying at a temperature of 30° C. to obtain the composite dressing having photothermal synergistic antibacterial repair properties.

[0035] The present invention also provides a use of the composite dressing with photothermal synergistic antibacterial repair as described in the present invention in preparing a wound repair medicine.

[0036] Beneficial effects of the present invention:

[0037] The composite dressing with photothermal synergistic antibacterial repair of the present invention uses polycaprolactone (PCL), bioactive glass (BG), tea polyphenols (TP) and black phosphorus (BP) as raw materials, and is prepared by electrospinning technology to have a Janus structure dressing with unidirectional water transfer properties. This dressing not only has excellent biocompatibility, but also exhibits significant photothermal antibacterial properties, can effectively promote the healing process of wounds, and is helpful for cell proliferation. The composite dressing with multiple functions has great potential for promotion and application, provides a new choice for clinical treatment, and has promotion and application value in the field of medical material technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Flow chart for the preparation of bioactive glass containing magnesium;

[0039] Figure 2 Flow chart for preparing PB / PT composite dressings for electrospinning;

[0040] Figure 3 Flow chart of preparation of PB / PTB composite dressing for electrospinning;

[0041] Figure 4 is the XRD pattern of the magnesium-containing bioactive glass (BG) prepared in Example 1;

[0042] Figure 5 The surface morphology and energy spectrum distribution result diagram of the magnesium-containing bioactive glass prepared in Example 1; wherein, Figure 5 A to 5C are SEM images of bioactive glass (BG) containing magnesium. Figure 5 D~5H are the energy spectrum distribution diagrams of bioactive glass (BG) containing magnesium;

[0043] Figure 6 A is the SEM image and diameter distribution diagram of PB composite fiber membranes with different magnesium-containing bioactive glass contents, where: Figure 6 A is the SEM image of bioactive glass (BG) containing magnesium at 2%. Figure 6 D is Figure 6 A magnified image. Figure 6 G is the diameter distribution diagram of bioactive glass (BG) containing 2% magnesium; Figure 6 B is the SEM image of bioactive glass (BG) containing magnesium at 4%. Figure 6 E is Figure 6 The enlarged image of B. Figure 6 H is the diameter distribution diagram of bioactive glass (BG) containing 4% magnesium; Figure 6 C is the SEM image of bioactive glass (BG) containing magnesium at 6%. Figure 6 F is Figure 6 The enlarged image of C. Figure 6 I is the diameter distribution diagram of bioactive glass (BG) containing 8% magnesium;

[0044] Figure 7 The SEM images and diameter distribution diagrams of PT composite fiber membranes with different tea polyphenol contents are shown in Figure 2. Figure 7 A is the SEM image of tea polyphenols (TP) at 5%, Figure 7 D is Figure 7 A magnified image. Figure 7 G is the diameter distribution diagram when tea polyphenols (TP) is 5%; Figure 7 B is the SEM image of tea polyphenols (TP) at 10%, Figure 7 E is Figure 7 The enlarged image of B. Figure 7 H is the diameter distribution diagram when tea polyphenols (TP) is 10%; Figure 7 C is the SEM image of tea polyphenols (TP) at 15%, Figure 7 F is Figure 7 The enlarged image of C. Figure 7 I is the diameter distribution diagram when tea polyphenols (TP) is 15%;

[0045] Figure 8The SEM images and diameter distribution diagrams of composite dressings with different black phosphorus contents are shown in Figure 2. Figure 8 A is a SEM image containing 150 μg / mL black phosphorus. Figure 8 B is Figure 8 A magnified image. Figure 8 C is the diameter distribution diagram containing 150 μg / mL black phosphorus; Figure 8 D is the SEM image containing 200 μg / mL black phosphorus. Figure 8 E is Figure 8 The enlarged image of D. Figure 8 F is the diameter distribution diagram containing 200 μg / mL black phosphorus;

[0046] Fig. 9 The SEM image, diameter distribution diagram and P element distribution diagram of the PTB composite fiber membrane prepared by using BP (200 μg / mL) and TP (10%) in Example 6, wherein: Fig. 9 A is the SEM image of the PTB composite fiber membrane doped with BP (200 μg / mL) and TP (10%). Fig. 9 B is Fig. 9 A magnified image. Fig. 9 C is the diameter distribution diagram, Fig. 9 D~9G are distribution diagrams of phosphorus;

[0047] Fig.10 The water contact angle results of PB composite fiber membranes with different magnesium-containing bioactive glass contents;

[0048] Fig.11 The water contact angle results of PT composite fiber membranes with different tea polyphenols contents;

[0049] Fig.12 The result diagram of water absorption is shown in Figure 2.

[0050] Fig.13 This is the tensile performance test result diagram;

[0051] Fig.14 is the TGA curve diagram;

[0052] Fig.15 The ion dissolution results of PB composite fiber membrane are shown in the figure, where: Fig.15 A is the dissolution of Ca element in the composite fiber membrane containing 6% BG at 12 hours, 1 day, 3 days and 5 days; Fig.15 B is the dissolution of Si element in the composite fiber membrane containing 6% BG at 12 hours, 1 day, 3 days and 5 days; Fig.15 C is the dissolution of P element in the composite fiber membrane containing 6% BG at 12 hours, 1 day, 3 days and 5 days; Fig.15D is the dissolution of Mg element in the composite fiber membrane containing 6% BG at 12 hours, 1 day, 3 days and 5 days;

[0053] Fig.16 The drug release results of the composite dressing are shown in Figure 2. Fig.16 A is the standard curve of tea polyphenols. Fig.16 B is the in vitro release curve of the composite dressing; the blue arrow indicates the time point of near-infrared irradiation;

[0054] Fig.17 This is the result of cell proliferation on PB composite fiber membrane;

[0055] Fig.18 This is the cell fluorescence result of PB composite fiber membrane;

[0056] Fig.19 This is the result of cell proliferation on PT composite fiber membrane;

[0057] Fig. 20 This is the cell fluorescence result of PT composite fiber membrane;

[0058] Fig.21 The figure is a comparison of the cell proliferation and cell fluorescence results of the PT composite fiber membrane and the PTB composite fiber membrane;

[0059] Fig. 22 This is the in vitro antibacterial test result of PT composite fiber membrane;

[0060] Fig.23 This is a comparison chart of the in vitro antibacterial test results of PT composite fiber membrane and PTB composite fiber membrane;

[0061] Fig.24 This is the result diagram of the forward and reverse infusion process of the double-layer dressing;

[0062] Fig.25 This is the result of the photothermal capacity test of the composite fiber membrane, where: Fig.25 A is the result of in vitro photothermal capacity detection. Fig.25 B is the result of the in vivo photothermal capacity detection;

[0063] Fig.26 This is the result diagram of wound repair effect, where: Fig.26 A is the wound healing photo at each time point; Fig.26 B is a diagram of the wound healing process of all groups;

[0064] Fig. 27 This is a quantitative analysis result diagram of rat wound healing, where: Fig. 27 A is the wound healing rate result graph; Fig. 27 B is the result diagram of the wound residual area;

[0065] Fig.28 The HE staining and analysis results of different dressing treatment groups are shown in Figure 1. Fig.28 A is the HE staining result at 7 days and 14 days. The red arrows indicate the hair follicles and sebaceous glands. Fig.28 B is the result diagram of the new epidermis length. Fig.28 C is the result diagram of hair follicle number. Fig.28 D is the wound surface distance result diagram;

[0066] Fig.29 The Masson staining and analysis results of different dressings on wounds are shown in Figure 1. Fig.29 A is the Masson staining result of samples collected at 7 days and 14 days. Fig.29 B is the result of collagen content analysis. DETAILED DESCRIPTION

[0067] The following will describe the embodiments of the present invention with reference to the preferred embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0068] If no specific techniques or conditions are specified in the specific embodiments, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0069] Example 1

[0070] like Figure 1 As shown, a method for preparing a PB composite fiber membrane comprises the following steps:

[0071] S1. Preparation of bioactive glass (BG) containing magnesium:

[0072] S11, in 3.73 mL of 0.2 M nitric acid aqueous solution, 15.855 g of tetraethyl orthosilicate (TEOS), 7.320 g of triethyl phosphate (TEP), 1.457 g of calcium nitrate tetrahydrate and 1.282 g of magnesium nitrate hexahydrate were sequentially added and dissolved, each time a raw material was added and dissolved for 45 min, and after all the raw materials were added, stirred for 1 h to obtain a sol solution;

[0073] S12, putting the sol solution into a polytetrafluoroethylene bottle, sealing it and leaving it at 37° C. for 3 days, so that the hydrolyzate forms a gel through cross-linking;

[0074] S13, aging the gel at 70° C. for 3 days, and then drying at 120° C. for 2 days to obtain a dry gel;

[0075] S14, placing the dry gel in a high-temperature box furnace, setting the heating rate to 2°C / min, heating the temperature to 600°C, and heat-treating the temperature for 3 hours, then cooling the mixture naturally, and grinding and sieving the mixture to obtain bioactive glass containing magnesium;

[0076] S2, adding 1.8 g of polycaprolactone (PCL) and 0.036 g, 0.072 g and 0.108 g of magnesium-containing bioactive glass (BG) to 10 mL of a mixed organic solvent of dichloromethane and N, N-dimethylformamide, stirring at a constant speed overnight to obtain a first mixed solution; wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent is 7:3;

[0077] S3. Preparation of PB composite fiber membrane: electrospinning the first mixed solution under light-proof conditions, and then placing the product in a vacuum drying oven and drying it at a temperature of 30° C. to fully remove the residual organic solvent in the fiber membrane, thereby obtaining a PB composite fiber membrane;

[0078] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0079] Example 2

[0080] like Figure 1 As shown, a method for preparing a PT composite fiber membrane comprises the following steps:

[0081] S1. Add 1.8 g of polycaprolactone (PCL) and 0.09 g, 0.18 g and 0.27 g of tea polyphenols (TP) respectively into 10 mL of a mixed organic solvent of dichloromethane and N, N-dimethylformamide, put them into a brown reagent bottle, and stir them at a constant speed overnight to obtain a second mixed solution, wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent is 7:3;

[0082] S3, preparation of PT composite fiber membrane: electrospinning the second mixed solution under light-proof conditions, and then placing the product in a vacuum drying oven and drying it at a temperature of 30° C. to fully remove the residual organic solvent in the fiber membrane, thereby obtaining a PT composite fiber membrane;

[0083] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0084] Example 3

[0085] like Figure 1 and Figure 2 As shown, a method for preparing a composite dressing with photothermal synergistic antibacterial repair comprises the following steps:

[0086] S1. Preparation of bioactive glass (BG) containing magnesium:

[0087] S11, in 3.73 mL of 0.2 M nitric acid aqueous solution, 15.855 g of tetraethyl orthosilicate (TEOS), 7.320 g of triethyl phosphate (TEP), 1.457 g of calcium nitrate tetrahydrate and 1.282 g of magnesium nitrate hexahydrate were sequentially added and dissolved, each time a raw material was added and dissolved for 45 min, and after all the raw materials were added, stirred for 1 h to obtain a sol solution;

[0088] S12, putting the sol solution into a polytetrafluoroethylene bottle, sealing it and leaving it at 37° C. for 3 days, so that the hydrolyzate forms a gel through cross-linking;

[0089] S13, aging the gel at 70° C. for 3 days, and then drying at 120° C. for 2 days to obtain a dry gel;

[0090] S14, placing the dry gel in a high-temperature box furnace, setting the heating rate to 2°C / min, heating the temperature to 600°C, and heat-treating the temperature for 3 hours, then cooling the mixture naturally, and grinding and sieving the mixture to obtain bioactive glass containing magnesium;

[0091] S2, adding 1.8 g of polycaprolactone (PCL) and 0.108 g of magnesium-containing bioactive glass (BG) to a mixed organic solvent of 10 mL of dichloromethane and N, N-dimethylformamide, stirring at a constant speed overnight to obtain a first mixed solution; wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent is 7:3;

[0092] 1.8 g of polycaprolactone (PCL) and 0.18 g of tea polyphenols (TP) were added to 10 mL of a mixed organic solvent of dichloromethane and N, N-dimethylformamide, placed in a brown reagent bottle, and stirred overnight at a constant speed to obtain a second mixed solution, wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent was 7:3;

[0093] S3. Preparation of PB / PT composite dressing: Under light-proof conditions, the first mixed solution is electrospun to obtain an inner nanofiber membrane; then the second mixed solution is electrospun onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane, and the product is placed in a vacuum drying oven and dried at a temperature of 30°C to fully remove the residual organic solvent in the fiber membrane to obtain a composite dressing with photothermal synergistic antibacterial repair, namely, a PB / PT composite dressing;

[0094] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0095] Example 4

[0096] like Figure 1 and Figure 3 As shown, a method for preparing a composite dressing with photothermal synergistic antibacterial repair comprises the following steps:

[0097] S1. Preparation of bioactive glass (BG) containing magnesium:

[0098] S11, in 3.73 mL of 0.2 M nitric acid aqueous solution, 15.855 g of tetraethyl orthosilicate (TEOS), 7.320 g of triethyl phosphate (TEP), 1.457 g of calcium nitrate tetrahydrate and 1.282 g of magnesium nitrate hexahydrate were sequentially added and dissolved, each time a raw material was added and dissolved for 45 min, and after all the raw materials were added, stirred for 1 h to obtain a sol solution;

[0099] S12, putting the sol solution into a polytetrafluoroethylene bottle, sealing it and leaving it at 37° C. for 3 days, so that the hydrolyzate forms a gel through cross-linking;

[0100] S13, aging the gel at 70° C. for 3 days, and then drying at 120° C. for 2 days to obtain a dry gel;

[0101] S14, placing the dry gel in a high-temperature box furnace, setting the heating rate to 2°C / min, heating the temperature to 600°C, and heat-treating the temperature for 3 hours, then cooling the mixture naturally, and grinding and sieving the mixture to obtain bioactive glass containing magnesium;

[0102] S2, adding 1.8 g of polycaprolactone (PCL) and 0.108 g of magnesium-containing bioactive glass (BG) to a mixed organic solvent of 10 mL of dichloromethane and N, N-dimethylformamide, stirring at a constant speed overnight to obtain a first mixed solution; wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent is 7:3;

[0103] 1.8 g of polycaprolactone (PCL), 0.18 g of tea polyphenols (TP) and black phosphorus (BP) were added to 10 mL of a mixed organic solvent of dichloromethane and N, N-dimethylformamide, placed in a brown reagent bottle, and stirred overnight at a constant speed to obtain a second mixed solution, wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent was 7:3, and the concentration of black phosphorus (BP) in the second mixed solution was 150 μg / mL;

[0104] S3. Preparation of PB / PTB composite dressing: Under light-proof conditions, the first mixed solution is electrospun to obtain an inner nanofiber membrane; then the second mixed solution is electrospun onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane, and the product is placed in a vacuum drying oven and dried at a temperature of 30°C to fully remove the residual organic solvent in the fiber membrane, thereby obtaining a composite dressing with photothermal synergistic antibacterial repair, namely, a PB / PT composite dressing;

[0105] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0106] Example 5

[0107] like Figure 1 and Figure 3 As shown, a method for preparing a composite dressing with photothermal synergistic antibacterial repair comprises the following steps:

[0108] S1. Preparation of bioactive glass (BG) containing magnesium:

[0109] S11, in 3.73 mL of 0.2 M nitric acid aqueous solution, 15.855 g of tetraethyl orthosilicate (TEOS), 7.320 g of triethyl phosphate (TEP), 1.457 g of calcium nitrate tetrahydrate and 1.282 g of magnesium nitrate hexahydrate were sequentially added and dissolved, each time a raw material was added and dissolved for 45 min, and after all the raw materials were added, stirred for 1 h to obtain a sol solution;

[0110] S12, putting the sol solution into a polytetrafluoroethylene bottle, sealing it and leaving it at 37° C. for 3 days, so that the hydrolyzate forms a gel through cross-linking;

[0111] S13, aging the gel at 70° C. for 3 days, and then drying at 120° C. for 2 days to obtain a dry gel;

[0112] S14, placing the dry gel in a high-temperature box furnace, setting the heating rate to 2°C / min, heating the temperature to 600°C, and heat-treating the temperature for 3 hours, then cooling the mixture naturally, and grinding and sieving the mixture to obtain bioactive glass containing magnesium;

[0113] S2, adding 1.8 g of polycaprolactone (PCL) and 0.108 g of magnesium-containing bioactive glass (BG) to a mixed organic solvent of 10 mL of dichloromethane and N, N-dimethylformamide, stirring at a constant speed overnight to obtain a first mixed solution; wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent is 7:3;

[0114] 1.8 g of polycaprolactone (PCL), 0.18 g of tea polyphenols (TP) and black phosphorus (BP) were added to 10 mL of a mixed organic solvent of dichloromethane and N, N-dimethylformamide, placed in a brown reagent bottle, and stirred overnight at a constant speed to obtain a second mixed solution, wherein the volume ratio of dichloromethane to N, N-dimethylformamide in the mixed organic solvent was 7:3, and the concentration of black phosphorus (BP) in the second mixed solution was 200 μg / mL;

[0115] S3. Preparation of PB / PTB composite dressing: Under light-proof conditions, the first mixed solution is electrospun to obtain an inner nanofiber membrane; then the second mixed solution is electrospun onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane, and the product is placed in a vacuum drying oven and dried at a temperature of 30°C to fully remove the residual organic solvent in the fiber membrane, thereby obtaining a composite dressing with photothermal synergistic antibacterial repair, namely, a PB / PT composite dressing;

[0116] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0117] Example 6

[0118] like Figure 1 As shown, a method for preparing a PT composite fiber membrane comprises the following steps:

[0119] S1. Add 1.8 g of polycaprolactone (PCL), 0.18 g of tea polyphenols (TP) and black phosphorus (BP) to 10 mL of a mixed organic solvent of dichloromethane and N,N-dimethylformamide, put the mixture into a brown reagent bottle, and stir at a constant speed overnight to obtain a second mixed solution, wherein the volume ratio of dichloromethane to N,N-dimethylformamide in the mixed organic solvent is 7:3, and the concentration of black phosphorus (BP) in the second mixed solution is 200 μg / mL;

[0120] S3, preparation of PTB composite fiber membrane: electrospinning the second mixed solution under light-proof conditions, and then placing the product in a vacuum drying oven and drying it at a temperature of 30° C. to fully remove the residual organic solvent in the fiber membrane, thereby obtaining a PTB composite fiber membrane;

[0121] The process parameters of electrospinning are as follows: the flow rate of the injection pump is 1.0 mL / h, the distance from the needle to the receiving device is 17 cm, the drum speed is 80 r / min, and the voltage is 14 kV.

[0122] Detection and analysis

[0123] 1) Phase analysis of magnesium-containing bioactive glass

[0124] X-ray diffraction analysis was performed on the magnesium-containing bioactive glass (BG) prepared in Example 1. The results are as follows: Figure 4 shown.

[0125] from Figure 4 From the analysis, it can be seen that the bioactive glass containing magnesium shows strong dispersibility after sintering, indicating that the material has amorphous structural characteristics. The diffraction peaks in the entire spectrum are relatively broad, and there are no sharp characteristic diffraction peaks, indicating that the bioactive glass obtained after high-temperature sintering is an amorphous inorganic material; there is a bun peak at the position of 2θ=23.6°, which corresponds to the amorphous structure of silicon dioxide in the bioactive glass.

[0126] 2) Surface morphology and energy spectrum distribution of magnesium-containing bioactive glass

[0127] The surface morphology, surface elements, energy spectrum analysis and element distribution analysis of the magnesium-containing bioactive glass (BG) prepared in Example 1 were performed using an energy dispersive spectrometer (EDS) in combination with a scanning electron microscope. The results are as follows: Figure 5 As shown and Table 1.

[0128] in, Figure 5 A to 5C are SEM images of bioactive glass (BG) containing magnesium. Figure 5 D~5H are elemental analysis diagrams of bioactive glass (BG) containing magnesium.

[0129] from Figure 5 It can be seen from observations in C~5C that the magnesium-containing bioactive glass (BG) particles present an amorphous block morphology at the micrometer scale, and it can be observed that silicon, magnesium, phosphorus, and calcium elements are evenly distributed in the scanning area.

[0130] from Figure 5 It can be seen from the observations in D~5H that each element is evenly distributed in the bioactive glass (BG) containing magnesium.

[0131] The elemental quantitative analysis of the bioactive glass (BG) containing magnesium is shown in Table 1.

[0132] Table 1 Quantitative analysis of elements in bioactive glass

[0133]

[0134] From the analysis in Table 1, it can be seen that the element distribution in the magnesium-containing bioactive glass (BG) is consistent with the theoretical preparation value (60SiO 2 -31CaO-4P 2 O 5 -5MgO) basically meets the requirements.

[0135] 3) Surface morphology and energy spectrum distribution of PB composite fibers

[0136] The surface morphology and energy spectrum of the PB composite fiber prepared in Example 1 were analyzed by scanning electron microscopy. The results are as follows: Figure 6 shown.

[0137] in, Figure 6 A is the SEM image of bioactive glass (BG) containing 2% magnesium (i.e., 0.036 g of BG is added). Figure 6 D is Figure 6 A magnified image. Figure 6 G is the diameter distribution diagram of the bioactive glass (BG) containing magnesium at 2% (i.e., 0.036 g of BG was added); Figure 6 B is the SEM image of bioactive glass (BG) containing 4% magnesium (i.e., 0.072 g of BG was added). Figure 6 E is Figure 6 The enlarged image of B. Figure 6 H is the diameter distribution diagram of the bioactive glass (BG) containing 4% magnesium (i.e., 0.072 g of BG was added); Figure 6 C is the SEM image of the bioactive glass (BG) containing 6% magnesium (i.e., 0.108 g of BG was added). Figure 6 F is Figure 6 The enlarged image of C. Figure 6 I is a diameter distribution diagram of the bioactive glass (BG) containing 6% magnesium (ie, 0.108 g of BG was added). Figure 6 In the graph, the percentage of bioactive glass (BG) containing magnesium is relative to polycaprolactone (PCL).

[0138] from Figure 6 The analysis shows that after doping with magnesium-containing bioactive glass (BG) powder, the fiber diameter of the PB composite fiber membrane is relatively uniform. The fiber diameter in the scanning electron microscope image was measured using ImageJ software, and the fiber diameter distribution diagram was drawn ( Figure 6GI), and the average diameter of each group of fibers was calculated. The average diameters of the PB composite fiber membranes containing 2% BG (i.e., 0.036g of BG was added), 4% BG (i.e., 0.072g of BG was added), and 6% BG (i.e., 0.108g of BG was added) were 1.32±0.52μm, 1.36±0.51μm, and 1.43±0.67μm, respectively. It can be found that the average diameter of the fiber membrane increases with the increase of BG content.

[0139] The surface morphology and energy spectrum of the PT composite fiber membrane prepared in Example 2 were analyzed by scanning electron microscopy. The results are as follows: Figure 7 shown.

[0140] in, Figure 7 A is the SEM image of tea polyphenols (TP) at 5% (i.e., 0.09 g of TP was added), Figure 7 D is Figure 7 A magnified image. Figure 7 G is the diameter distribution diagram when tea polyphenols (TP) is 5% (i.e., 0.09 g of TP is added); Figure 7 B is the SEM image of tea polyphenols (TP) at 10% (i.e., 0.18 g of TP was added). Figure 7 E is Figure 7 The enlarged image of B. Figure 7 H is the diameter distribution diagram when tea polyphenols (TP) is 10% (i.e., 0.18 g of TP is added); Figure 7 C is the SEM image of tea polyphenols (TP) at 15% (i.e., 0.27 g of TP was added). Figure 7 F is Figure 7 The enlarged image of C. Figure 7 I is the diameter distribution diagram when the tea polyphenol (TP) content is 15% (ie, 0.27 g of TP is added). Figure 7 In the figure, the percentage of tea polyphenols (TP) is relative to polycaprolactone (PCL).

[0141] from Figure 7 From the analysis, it can be seen that with the increase of TP addition content, the fiber diameter tends to increase. From the microscopic morphology, the fiber with 10% TP content is more uniform. In the electron microscope image of the PT composite fiber membrane containing 15% TP, flat and wide nanofibers were found. This is because the addition of more TP leads to the untimely evaporation of the solvent in the electrospinning solution during the spinning process, so the fiber presents a flattened morphology. By using ImageJ software to randomly select the fiber diameter for measurement, a diameter distribution diagram is drawn ( Figure 7 G-7I), and the average fiber diameter was calculated by Origin software. The average fiber diameters of 5% TP, 10% TP, and 15% TP were 0.52±0.25 μm, 0.82±0.38 μm, and 2.11±0.69 μm, respectively.

[0142] The surface morphology and energy spectrum analysis of the composite dressings prepared in Example 4 and Example 5 were performed using a scanning electron microscope. The results are as follows: Figure 8 shown.

[0143] in, Figure 8 A is a SEM image of 150 μg / mL black phosphorus prepared in Example 4. Figure 8 B is Figure 8 A magnified image. Figure 8 C is the diameter distribution diagram containing 150 μg / mL black phosphorus prepared in Example 4; Figure 8 D is a SEM image of the sample containing 200 μg / mL black phosphorus prepared in Example 5. Figure 8 E is Figure 8 The enlarged image of D. Figure 8 F is the diameter distribution diagram of 200 μg / mL black phosphorus prepared in Example 5.

[0144] from Figure 8 The analysis showed that the fiber diameter of the composite dressing was significantly reduced (the average diameters of 150 μg / mL and 200 μg / mL BP were 0.21±0.06 μm and 0.23±0.10 μm, respectively). Since BP is dispersed in N-methylpyrrolidone (NMP) solution, the addition of NMP has a certain effect on the electrospinning of polycaprolactone polymer, making its fiber diameter much smaller than that of the dichloromethane (DCM) and N,N-dimethylformamide (DMF) solvent systems.

[0145] The microstructure and P element distribution of the PTB composite fiber membrane doped with BP (200 μg / mL) and TP (10%) prepared in Example 6 are as follows: Fig. 9 shown.

[0146] in, Fig. 9 A is the SEM image of the PTB composite fiber membrane doped with BP (200 μg / mL) and TP (10%). Fig. 9 B is Fig. 9 A magnified image. Fig. 9 C is the diameter distribution diagram, Fig. 9 D~9G are the distribution diagrams of phosphorus element.

[0147] from Fig. 9 The analysis shows that the average diameter of the PTB composite fiber membrane is 0.24±0.08μm, which is similar to the diameter of the fiber membrane simply doped with BP. From the results of the energy spectrometer surface scan (9D-G), it can be seen that the block agglomerates (yellow arrows) in the SEM image of the fiber membrane may be caused by the agglomeration of black phosphorus.

[0148] 4) Wettability test

[0149] The surface hydrophilicity and hydrophobicity of the PB composite fiber membrane prepared in Example 1 and the PT composite fiber membrane prepared in Example 2 were detected by using a contact angle meter. The contact angle between the sample and water is recorded as θ. When θ>90°, it is hydrophobic, and when θ<90°, it is hydrophilic. The larger or smaller θ is, the more hydrophobic or hydrophilic the sample is. The results are shown in Figure 2. Fig.10 and Fig.11 shown.

[0150] from Fig.10 From the analysis, we can see that the contact angle of pure PCL is as high as 120.52±1.06°, which is a hydrophobic material. When BG is added, it is found that the hydrophilicity of the fiber membrane has been improved to a certain extent, and the hydrophilicity of the material is improved, which is conducive to improving the hygroscopicity of the material and better meeting the requirements of composite skin wound repair materials. However, the contact angle is greater than 90°, which has hydrophobic properties and can reduce the adhesion between the wound and the dressing.

[0151] from Fig.11 From the analysis, we can see that the water contact angle of the fiber membrane containing tea polyphenols (TP). The water contact angles of the fiber membrane containing 5%, 10% and 15% TP at 5s were 62.32±0.06°, 61.65±0.24° and 36.47±0.21° respectively. With the increase of TP content, the time for the fiber membrane to reach a completely hydrophilic state (that is, the water contact angle is 0) is shorter. This is because TP contains a large amount of hydrophilic phenolic hydroxyl groups.

[127] , which makes the fiber membrane containing TP have good hydrophilicity.

[0152] 5) Water absorption test

[0153] Exudate and tissue fluid from the wound need to be treated to prevent excessive accumulation of fluid between the wound and the dressing, which could lead to infection. Therefore, it is important to choose a wound dressing that has good exudate absorption properties.

[0154] The water absorption rate test of the composite fiber membrane is as follows: the composite fiber membrane is made into a 1cm×1cm thin sheet, and the mass of the fiber membrane is first weighed with an electronic balance as m 0 (g) Then, place the samples in centrifuge tubes containing phosphate buffered saline (PBS), place the centrifuge tubes containing the samples and PBS in a 37°C oven, and take out the samples every 1, 3, 5, 7, 9, and 11 hours. Gently wipe off the surface moisture, weigh, and record the mass m i (g), water absorption is recorded as W a :

[0155]

[0156] The water absorption rate of pure PCL, the PB composite fiber membrane prepared in Example 1, the PT composite fiber membrane prepared in Example 2, and the composite dressings prepared in Examples 3 and 4 were tested. The results are as follows: Fig.12 shown.

[0157] in, Fig.12 A is the water absorption rate of PB composite fiber membranes with different magnesium-containing bioactive glass contents; Fig.12 B is the water absorption rate of PT composite fiber membranes with different tea polyphenols contents; Fig.12 C is the water absorption rate of the PB / PT composite dressing prepared in Example 3 and the PB / PTB composite dressing prepared in Example 4.

[0158] from Fig.12 A and Fig.12 From the analysis in B, it can be seen that the highest water absorption rate of the hydrophobic fiber membrane group (doped with BG) is 259.16±7.31%, while the highest water absorption rate of the hydrophilic fiber membrane group (doped with TP) is 696.03±7.43%. Both groups of fiber membranes meet the 100%-900% water absorption rate required for ideal wound dressings. Fig.12 From the analysis in C, it can be seen that the water absorption rate of the two groups of composite fiber membranes PB / PT and PB / PTB gradually increased after being immersed in PBS solution for 1, 3, 5, 7, 9 and 11 hours. This may be because the fiber diameter of the fiber membrane in the BP group is finer, resulting in a decrease in porosity, so the water absorption rate of PB / PTB is slightly lower.

[0159] 5) Tensile performance test

[0160] The mechanical properties of the composite fiber membrane prepared in Example 1, the composite fiber membrane prepared in Example 2, the composite dressing prepared in Example 3, and the composite dressing prepared in Example 5 were tested to analyze the influence of the breaking strength and breaking elongation of each group of fiber membranes. The test results are as follows: Fig.13 shown.

[0161] in, Fig.13 A is the tensile performance structure of PB composite fiber membranes with different magnesium-containing bioactive glass contents (i.e., Example 1); Fig.13 B is the tensile performance structure of PT composite fiber membranes with different tea polyphenol contents (i.e., Example 2); Fig.13 C is the tensile performance structure of the PB / PT composite dressing prepared in Example 3 and the PB / PTB composite dressing prepared in Example 5.

[0162] from Fig.13From the analysis of A and 13B, it can be seen that the PCL fiber membrane itself has good mechanical properties, with a breaking strength of 4.54±0.84MPa and a breaking elongation of 604.33±68%. The doping of drugs in the hydrophobic membrane (Example 1) and the hydrophilic membrane (Example 2) is only a physical combination. Since there are significant differences in the mechanical properties between tea polyphenols, bioactive glass and polycaprolactone, when the modified fiber membrane is stretched, the breaking strength and breaking elongation of the sample will decrease significantly due to stress concentration. Fig.13 The analysis in C shows that due to the doping of black phosphorus, the mechanical properties of the PB / PTB group are significantly lower than those of the PB / PT group ( Fig.13 C), but still meets the mechanical strength requirement of 1-2MPa for skin wound dressings.

[0163] 6) Thermogravimetric analysis

[0164] The PB composite fiber membrane doped with different amounts of magnesium-containing bioactive glass in Example 1 was subjected to thermogravimetric analysis using a thermogravimetric analyzer. The results are as follows: Fig.14 shown.

[0165] in, Fig.14 A is the TGA curve of PB composite fiber membrane, Fig.14 B is Fig.14 Enlarged view of 500℃~700℃ in A.

[0166] from Fig.14 It can be seen from the analysis that when the temperature reaches 300°C, the polymer polycaprolactone in the composite fiber membrane undergoes thermal decomposition, and each group of samples with different magnesium-containing bioactive glass contents all show thermal weight loss. After 500°C, since BG does not thermally degrade at this temperature and the content of BG in each group of composite fiber membranes is different, as the temperature rises, each group of composite fiber membranes suffers different degrees of mass loss. Finally, the mass percentage of BG in each composite fiber membrane was measured to be 1.86%, 3.42% and 4.59%. Due to the sedimentation of BG during the spinning process, the measured value is less than the theoretical value in the spinning solution.

[0167] 7) Ion dissolution test of composite nanofiber membrane

[0168] Active ions of Ca, Si, P, and Mg can be released from the Si-O network of bioactive glass through hydrolysis reaction. Active ions of Ca, Si, P, and Mg can help the rapid formation of granulation tissue at the wound site of the skin. This shows that the release of active ions is very important for promoting wound repair. Therefore, the composite fiber membrane doped with 6% magnesium-containing bioactive glass in Example 1 was tested for ion dissolution. The results are shown in Figure 1. Fig.15 shown.

[0169] in, Fig.15 A is the dissolution of Ca element in the composite fiber membrane containing 6% BG (i.e., 0.108 g of BG was added) at 12 hours, 1 day, 3 days, and 5 days; Fig.15 B is the dissolution of Si element in the composite fiber membrane containing 6% BG (i.e., 0.108 g of BG was added) at 12 hours, 1 day, 3 days, and 5 days; Fig.15 C is the dissolution of P element in the composite fiber membrane containing 6% BG (i.e., 0.108 g of BG was added) at 12 hours, 1 day, 3 days, and 5 days; Fig.15 D is the dissolution of Mg element in the composite fiber membrane containing 6% BG (ie, 0.108 g of BG was added) in 12 hours, 1 day, 3 days and 5 days.

[0170] from Fig.15 The analysis shows that the 12h ion dissolution data show that the ion concentrations of Ca, Si, and Mg elements increased because the bioactive glass was soluble when immersed in SBF. However, the P element basically showed a downward trend because it participated in the mineralization to form hydroxyapatite, which would cause the loss of the P element. The element dissolution conditions of 1 day, 3 days, and 5 days showed that the active ions in the composite membrane were continuously released and showed an upward trend. The above phenomena show that BG doped into the nanofiber membrane can continuously and effectively release active ions and promote wound repair.

[0171] 8) Drug release from nanofiber membranes

[0172] In vitro release of tea polyphenols

[0173] (1) Preparation of tea polyphenols standard curve

[0174] Weigh tea polyphenols (TP) accurately, dissolve TP in PBS solution, and prepare solutions of different concentrations (0.1, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4, 12.8 μg / mL). Test the absorbance at 274 nm, with 3 sets of parallel samples. Perform curve fitting on drug absorbance and solution concentration, make a standard curve of tea polyphenols, and obtain the linear regression equation. The results are as follows: Fig.16 As shown in A.

[0175] (2) In vitro release of tea polyphenols

[0176] The composite dressings prepared in Example 3 and Example 5 were made into 1 cm × 1 cm samples, and three parallel samples were set. 10 mg of nanofiber membrane was soaked in a brown bottle containing 10 mL of PBS and placed in a 37 ° C shaker. Under the condition of 100 rpm / min, 3 mL of solution was drawn and an equal amount of fresh release solution was added at 0, 6, 12, 18, 24, 36, 48, 72, 96, 120, 144, 168, 192, and 216 h. Unlike the PB / PT group, the PB / PTB group needs to be irradiated with near-infrared light for 4 minutes at a specific time (0, 1, 3, 5, and 7 days) to explore the effect of photothermal effect on drug release. The absorbance of the sample sustained-release solution at 274 nm was tested using a UV-visible spectrophotometer. The release rate of tea polyphenols in the material was calculated according to the tea polyphenols standard curve (y=0.02252x-0.00656, R2=0.9991) and formula (1):

[0177]

[0178] Among them, WR is the cumulative drug release percentage, Wt is the drug release amount at different time points, and W0 is the drug content in the fiber membrane.

[0179] The results are as follows Fig.16 As shown in B.

[0180] from Fig.16 Analysis in B shows that the cumulative release of tea polyphenols in the PB / PT group reached 49.81±2.13% on the 1.5th day, while the release rate in the PB / PTB group reached 60.98±1.84% due to the stimulation of near-infrared light. The drug release rate of both groups tended to be flat after the 4th day. On the 9th day of the test, the release rates of the two groups of dressings were 78.12±2.77% and 83.02±2.79%, respectively, indicating that near-infrared light irradiation helps promote a more complete release of tea polyphenols.

[0181] 9) Cytological characterization

[0182] Cell proliferation experiment: The proliferation status of L929 cells on pure PCL and composite fiber membranes with different BG contents in Example 1, composite fiber membranes with different TP contents in Example 2, and PTB composite fiber membranes were quantitatively detected and analyzed using the CCK-8 method, and the kit was Cell Counting Kit-8. The experimental steps are as follows:

[0183] 10,000 cells were seeded in each well of a 24-well plate, and the culture medium was replaced every 2 days.

[0184] According to the instructions of the CCK-8 kit, the required 10% CCK-8 test solution was prepared, with three parallel samples in each group. The specific operation was to mix 100 μL of CCK-8 stock solution and 900 μL of complete culture medium evenly, and the test solution was prepared and used immediately. The above operations were all carried out under light-proof conditions.

[0185] On the 1st, 3rd, 5th and 7th days after the cells and the composite fiber membrane (or extract) were co-cultured, the culture medium was discarded, the cells were washed 3 times with PBS, and 200 μL of CCK-8 detection solution was added to each group of wells. The well plate was then covered with aluminum foil and placed at 37°C and 5% CO 2 Incubate in a dark incubator for 2 h.

[0186] After incubation for 2 hours in the dark, 150 μL of culture medium was aspirated from each well and added to a new 96-well plate. The optical density (450 nm) of each well was measured using an ELISA reader. Fig.17 , Fig.19 and Fig.21 As shown in A.

[0187] The results of cell fluorescence staining with calcein were as follows: Fig.18 , Fig. 20 and Fig.21 As shown in B.

[0188] from Fig.17 and Fig.18 From the analysis, we can see that the absorbance value of PCL fiber membrane is the lowest, which may be due to the hydrophobic property of the material, which is not conducive to cell adhesion. However, compared with the blank group (TCP group), the absorbance is very different, which can illustrate the good biocompatibility of PCL itself. The fiber membranes of each group doped with bioactive glass (BG) have the ability to promote cell proliferation, and the fiber membrane with a content of 6% BG has the best ability to promote proliferation.

[0189] from Fig.19 and Fig. 20 The analysis showed that TP promoted cell proliferation. When the TP concentration reached 15%, the proliferation of L929 cells was slightly lower than that of the 10% concentration.

[0190] from Fig.21 From the analysis, it can be seen that the composite fiber membrane prepared with 10% TP and the PTB composite fiber membrane prepared with 10% TP and 200 μg / mL BP (i.e., the PTB composite fiber membrane prepared in Example 6) were selected. The CCK-8 results showed that the cell activity of the fiber membrane containing BP was slightly lower. This is because the degradation product of BP is phosphate, which shows extremely low toxicity to cells but is harmless to the human body.

[0191] As can be seen from the above, the results of CCK-8 and cell fluorescence images both show that the above fiber membranes have no obvious toxicity to L929 cells.

[0192] 10) In vitro antibacterial test

[0193] The main cause of delayed wound healing includes infection with pathogenic microorganisms, with Escherichia coli and Staphylococcus aureus being two of the most common bacteria. Therefore, ideal wound dressings should have antibacterial properties.

[0194] In this study, the inhibition zone method was used to determine the inhibitory effect of nanofiber membrane on E. coli and S. aureus.

[0195] The in vitro antibacterial properties of the composite fiber membrane were studied using the inhibition zone method and the co-culture plate coating method. The specific steps are as follows:

[0196] Inhibition zone method

[0197] (1) Sample processing: Composite fiber membranes with TP contents of 0%, 5%, 10%, and 15% (i.e., Example 2) were prepared. According to the provisions of GB21510-2008, PCL fiber membranes with different tea polyphenol contents were cut into standard samples with a diameter of 1 cm. All samples were sterilized under ultraviolet light for 30 min in a clean bench for subsequent use.

[0198] (2) Culture medium preparation: ① LB liquid culture medium: add 2.5 g LB broth culture medium to 100 mL distilled water, sterilize at high temperature and high pressure for 15 min and set aside; ② LB solid culture medium: add 2.5 g LB broth culture medium and 1.5 g agar powder to 100 mL distilled water, sterilize at high temperature and high pressure for 15 min, cool to about 40°C-45°C, and pour into a disposable sterile culture dish.

[0199] (3) Preparation of bacterial suspension stock solution: inoculate the working strain (Escherichia coli, Staphylococcus aureus) into LB liquid culture medium and culture at 37°C for about 12h-14h.

[0200] (4) Take the bacterial suspension diluted 10 times in step (3) and continue to dilute until the final concentration is adjusted to 1.0×105 CFU / mL. Spread evenly on LB solid medium (100 μL of dilution), place the sterilized fiber membrane on the surface, and incubate in a 37°C constant temperature incubator for 24 hours.

[0201] (5) Calculation of the inhibition zone: Use a ruler to measure the diameter of the inhibition zone, measure three times in different directions, and take the average value.

[0202] Co-culture plate spread method

[0203] (1) Sample pretreatment: Refer to GB / T20944,3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method" to test the antibacterial properties of the samples. Weigh 50 mg of the sample, place it in a bacterial culture tube with the corresponding number, and sterilize it under ultraviolet light for 30 minutes.

[0204] (2) The steps for preparing the culture medium are the same as above.

[0205] (3) The steps for preparing the bacterial suspension stock solution are the same as above.

[0206] (4) Inoculation and incubation of experimental samples: Take 100 μL of diluent (1×105 CFU / mL), add 5 mL of LB liquid culture medium and 50 μL of diluted bacterial solution to the corresponding numbered bacterial culture tubes, at which the sample concentration is 10 mg / mL. No sample is added to the blank group. Incubate at 37°C, 200 rpm / min, and shake for 6 hours. After the incubation, dilute the bacterial solution continuously by 107 and evenly spread it on the LB solid culture medium (100 μL of diluent). Incubate at 37°C for 18 hours.

[0207] (5) Take photos of the colonies, count them, and calculate the inhibition rate using Formula 2:

[0208]

[0209] Where B: inhibition rate; Bd: number of colonies in the blank group; B0: number of colonies in the experimental group.

[0210] The results are as follows Fig. 22 shown.

[0211] in, Fig. 22 A is the result of the inhibition zone of E.coli. Fig. 22 B is the result of the inhibition zone against S. aureus. Fig. 22 C is the statistical result diagram of the diameter of the inhibition zone.

[0212] Fig. 22 In the experiment, the size of the inhibition zone represents the antibacterial ability of the drug. Fig. 22The analysis shows that the PCL membrane has no obvious antibacterial activity. Statistical analysis shows that the diameters of the inhibition zones of 5% TP, 10% TP and 15% TP for E. coli are 1.19±0.38mm, 1.25±0.85mm, 2.29±0.48mm, respectively, and the diameters of the inhibition zones for S. aureus are 1.51±0.52mm, 2.06±0.54mm, 2.97±0.59mm, respectively. The diameter of the inhibition zone of the nanofiber membrane increases with the increase of TP content. This is because the increase in TP increases the release amount and the stronger the antibacterial effect. The results show that tea polyphenols have antibacterial activity against both E. coli and S. aureus, but the antibacterial activity against S. aureus is stronger.

[0213] The above studies show that tea polyphenol fiber membrane has antibacterial properties, but due to the high concentration of bacterial solution in the experiment and the limitation of drug dissolution in the fiber membrane, we further co-cultured the material and bacterial solution and used the plate coating method to study the antibacterial activity of PT and PTB composite fiber membrane (i.e., the PTB composite fiber membrane prepared in Example 6). The results are as follows Fig.23 shown.

[0214] Fig.23 A~ Fig.23 C is the result of the inhibition zone of E.coli. Fig.23 D~ Fig.23 F is the result diagram of the inhibition zone against S. aureus.

[0215] from Fig.23 As can be seen from the figure, the blank group has no antibacterial effect. The images of the agar plate show that the PT and PTB composite fiber membranes have direct antibacterial activity against E. coli and S. aureus. Fig.23 The presence of a single strain was observed in B, while Fig.23 There are no colonies in C, which is because BP can convert light energy into sufficiently high temperature under near-infrared irradiation, thus causing devastating damage to bacteria. This result shows that the PTB composite fiber membrane has good photothermal antibacterial properties.

[0216] 11) Janus water transmission characterization

[0217] Water droplets were added to the surface of the PB / PTB dressing prepared in Example 5, and the water transfer process on both sides of the hydrophilic (Hp) fiber membrane and the hydrophobic (Hb) fiber membrane was observed. Fig.24 shown.

[0218] Fig.24 A is the water absorption test of janus membrane, Fig.24 B is the forward and reverse liquid transport process.

[0219] from Fig.24 It can be seen from the analysis that the added water droplets can be transferred from the hydrophobic side to the hydrophilic side, while the water droplets on the hydrophilic side will not be transferred to the hydrophobic side. Due to the presence of the hydrophobic fiber membrane, the structure can only transfer water in one direction, which can prevent the reverse osmosis of liquid. This proves that the double-layer Janus structure wound dressing prepared by the present invention can transfer liquid in one direction from the inside (hydrophobic layer) to the outside (hydrophilic layer), and the hydrophobic layer in contact with the skin can prevent the reverse osmosis of liquid and reduce the possibility of wound infection.

[0220] 12) Analysis of near infrared response characteristics

[0221] Photothermal agents that convert light energy into heat energy have the basic properties of sterilization, reducing inflammation, and promoting microcirculation.

[0222] Near-infrared photothermal performance of fiber membrane containing 200ug / mL BP, using infrared thermal imaging, experimental parameters are 808nm, 1.0W / cm 2 , 4min. The results are as follows Fig.25 shown.

[0223] in, Fig.25 A is the image result of in vitro photothermal capability. Fig.25 B is the in vivo photothermal capability image result.

[0224] from Fig.25 From the analysis in A, it can be seen that as the near-infrared light irradiation time increases, the temperature of the fiber membrane containing BP increases significantly, but there is no significant change in the blank group (NC). Under the stimulation of NIR, the temperature of the fiber membrane in vivo and in vitro can exceed 50°C, which can kill bacteria. At 50°C, most bacteria will be killed due to membrane rupture, partial enzyme and protein destruction. We placed the fiber membrane on the wound of rats to further evaluate the photothermal effect of the fiber membrane containing BP in vivo. Fig.25 As shown in B, the temperature of the wound area of ​​the fiber membrane containing BP increased from 29.7°C to 51.5°C, while the temperature of the blank group (NC) only increased by 5.4°C. This proves that BP has good photothermal conversion ability in vivo.

[0225] 13) Analysis of wound repair effect

[0226] A rat full-thickness skin defect model was constructed to evaluate the wound healing effects of the PB / PT composite dressing prepared in Example 3 and the PB / PTB composite dressing prepared in Example 5. Wound healing photos were taken at each time point. The results are shown in Figure 2. Fig.26 A. The wound healing process of all groups was as shown in Fig.26 As shown in B.

[0227] from Fig.26 A and Fig.26The analysis in B showed that the wound sizes of the blank group and PCL group on days 3, 11, and 14 were significantly higher than those of the PB / PT group and PB / PTB group.

[0228] The wound size and wound healing rate were used as evaluation criteria. Fig. 27 shown.

[0229] in, Fig. 27 A is the wound healing rate result diagram, Fig. 27 B is the result diagram of wound residual area.

[0230] from Fig. 27 The analysis showed that after the third day of treatment with composite dressing, the wound healing rates of the PB / PT group and the PB / PTB group were significantly better than those of the other groups. On the seventh day, the wound healing rates of the blank group, PCL group, PB / PT group, and PB / PTB group were 34.96±3.92%, 49.71±4.35%, 54.19±4.27%, and 65.41±2.12%, respectively. As the repair time prolonged, the wounds of the PB / PT group (99.62±3.42%) and the PB / PTB group (99.77±1.30%) healed faster and were basically healed on the 14th day, which was significantly different from the blank group (93.18±3.57%) and the PCL group (93.28±2.82%).

[0231] 14) H&E staining observation

[0232] Newly grown epidermis, number of hair follicles, and wound distance were measured and analyzed on H&E-stained wound tissue sections. Fig.28 shown.

[0233] in, Fig.28 A is the HE staining result on the 7th and 14th days. The red arrows indicate the hair follicles and sebaceous glands. Fig.28 B is the result diagram of the new epidermis length. Fig.28 C is the result diagram of hair follicle number. Fig.28 D is the wound surface distance result diagram.

[0234] from Fig.28 A and Fig.28 The analysis in D shows that the wound distance of the PB / PT group (corresponding to the PB / PT composite dressing prepared in Example 3) and the PB / PTB group (corresponding to the PB / PT composite dressing prepared in Example 5) on the 7th day was reduced compared with the blank group and the PCL group. Fig.28 From the analysis in A, we can see that newly generated epidermal tissue can be observed in the wound tissue sections. The re-epithelialization distance of the PB / PT group and the PB / PTB group is greater than that of the blank group and the PCL group, which means that the re-epithelialization is faster. Fig.28From the analysis in C, we can see that hair follicles were formed in the PB / PT group and the PB / PTB group on the 14th day, and they were more than those in the other groups. Fig.28 From the analysis in A, it can be seen that the PB / PT and PB / PTB treatment groups have more hair follicles and sebaceous glands, which are typical characteristics of mature skin.

[0235] 15) Masson staining observation

[0236] The wound tissue sections of each group were stained with Masson trichrome to measure the collagen volume fraction (CVF), and the measurement results were quantitatively analyzed. Fig.29 shown.

[0237] in, Fig.29 A is the Masson staining result of samples collected at 7 days and 14 days. Fig.29 B is the result of collagen content analysis.

[0238] from Fig.29 The analysis in A shows that the colors of the PB / PT group (corresponding to the PB / PT composite dressing prepared in Example 3) and the PB / PTB group (corresponding to the PB / PT composite dressing prepared in Example 5) are bluer than those of the blank group and the PCL group. As the treatment time increases, the collagen in each group increases. Fig.29 Analysis in B shows that on the 14th day, the collagen volume fractions in the PB / PT group (71.79±0.82%) and the PB / PTB group (73.43±7.97%) increased significantly compared with the blank group (48.51±4.39%) and the PCL group (54.62±4.05%), indicating that in the process of wound healing, the dressings with bioactive glass (BG), tea polyphenols (TP) and black phosphorus (BP) have the ability to accelerate collagen deposition and promote tissue remodeling. The above results show that the BG, TP and BP added to the PB / PT group and PB / PTB can make the dressings have antibacterial functions and promote wound tissue repair. BP can cooperate with TP to fight bacteria under the irradiation of near-infrared light, providing a healthy regenerative microenvironment for wound recovery.

[0239] The composite dressing with photothermal synergistic antibacterial repair of the present invention is prepared with polycaprolactone (PCL), bioactive glass (BG), tea polyphenols (TP) and black phosphorus (BP) as raw materials to prepare a wound dressing with photothermal and drug synergistic antibacterial repair. By preparing different samples, their physicochemical properties, cell biological properties, antibacterial properties and in vivo wound healing experiments were studied, and the following conclusions were obtained: (1) XRD and EDS results showed that bioactive glass containing magnesium was successfully prepared by the sol-gel method; (2) SEM results showed that nanofiber membranes with good morphology were successfully prepared by electrospinning; (3) Mechanical results showed that although the fiber membrane showed mechanical loss after doping with drugs. However, it still meets the mechanical strength requirement of 1-2MPa required for skin wound dressings; (4) Contact angle and water transfer tests show that the PCL fiber membrane with TP has good hydrophilicity, and a Janus structure dressing with unidirectional water transfer properties was prepared by electrospinning technology; (5) Cytological evaluation shows that the fiber membranes with TP, BG and BP have good biocompatibility and can promote cell proliferation; (6) In vitro antibacterial experiments show that the fiber membrane with TP has good antibacterial properties, and the fiber membrane with BP has good photothermal antibacterial properties under the stimulation of near-infrared light; (7) The results of the wound healing experiment of the full-thickness skin defect model of SD rats show that the optical images of the wound healing process, H&E staining and Masson trichrome staining of the wound tissue all verify the good effect of the PB / PT group and the PB / PTB group in promoting wound healing. In summary, this chapter successfully prepared a wound dressing with good biocompatibility, photothermal and drug synergistic antibacterial properties, which has promotion and application value in the field of medical material technology.

[0240] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A composite dressing with photothermal synergistic antibacterial repair, characterized in that: It is composed of an inner nanofiber membrane and an outer nanofiber membrane; The inner nanofiber membrane is composed of polycaprolactone (PCL) and bioactive glass (BG) containing magnesium; The outer nanofiber membrane is composed of polycaprolactone (PCL), tea polyphenols (TP) and black phosphorus (BP); The composite dressing is a Janus structure dressing with a unidirectional water transfer property, the inner nanofiber membrane is a hydrophobic layer, and the outer nanofiber membrane is a hydrophilic layer, so as to unidirectionally transfer liquid from the hydrophobic layer to the hydrophilic layer, and the hydrophobic layer in contact with the skin can prevent liquid reverse osmosis; The mass percentage of the polycaprolactone (PCL) and the magnesium-containing bioactive glass (BG) is 94% to 98%: 2% to 6%; The mass percentages of the polycaprolactone (PCL) and tea polyphenols (TP) are 85%-95%: 5%-15%.

2. A method for preparing the composite dressing with photothermal synergistic antibacterial repair as claimed in claim 1, characterized in that: The following steps are involved: adding polycaprolactone (PCL) and bioactive glass (BG) containing magnesium into an organic solvent to obtain a first mixed solution; adding polycaprolactone (PCL), tea polyphenols (TP) and black phosphorus into an organic solvent to obtain a second mixed solution; Electrospinning the first mixed solution to obtain an inner nanofiber membrane; The second mixed solution is electrospun onto the inner nanofiber membrane to form an outer nanofiber membrane on the inner nanofiber membrane, thereby obtaining a composite dressing with photothermal synergistic antibacterial repair.

3. The preparation method according to claim 2, characterized in that: The method for preparing the magnesium-containing bioactive glass comprises: dissolving tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and magnesium nitrate hexahydrate in a nitric acid aqueous solution in sequence to obtain a sol solution; The sol solution is sealed and allowed to stand to obtain a gel; The gel is aged, dried and heat treated to obtain a magnesium-containing bioactive glass.

4. The preparation method according to claim 3, characterized in that: The molar ratio of tetraethyl orthosilicate (TEOS), triethyl phosphate (TEP), calcium nitrate tetrahydrate and magnesium nitrate hexahydrate is 55-65:6-10:29-33:2-8; And / or, the concentration of nitric acid in the aqueous nitric acid solution is 0.18M~0.22M; And / or, the sealed and static temperature is 37° C., and the sealed and static time is 3 days; And / or, the aging temperature is 70° C. and the aging time is 3 days; And / or, the drying temperature is 120° C. and the drying time is 2 days; And / or, the temperature of the heat treatment is 600° C., the time of the heat treatment is 3 hours, the heating method of the heat treatment is programmed heating, and the heating rate of the programmed heating is 2° C. / min.

5. The preparation method according to claim 2, characterized in that: The concentration of the black phosphorus (BP) in the second mixed solution is 150 μg / mL to 200 μg / mL.

6. The preparation method according to claim 2, characterized in that: The electrospinning process parameters were as follows: syringe pump flow rate of 1.0 mL / h, distance from needle to receiving device of 17 cm, drum speed of 80 r / min, and voltage of 14 kV; And / or, the electrospinning is carried out under light-proof conditions.

7. The preparation method according to claim 2, characterized in that: The organic solvent is a mixed solvent of dichloromethane and N,N-dimethylformamide; The volume ratio of dichloromethane to N,N-dimethylformamide in the mixed solvent is 7:3; And / or, after forming the outer layer of nanofiber membrane on the inner layer of nanofiber membrane, the method further comprises: vacuum drying at a temperature of 30° C. to obtain the composite dressing having photothermal synergistic antibacterial repairing properties.

8. Use of the composite dressing with photothermal synergistic antibacterial repair as claimed in claim 1 in preparing a wound repair medicine.

Citation Information

Patent Citations

  • Multi-component double-layer composite nano-film dressing and production method thereof

    CN112569397A

  • Electrostatic spinning composite nanofiber material as well as preparation method and application thereof

    CN115679541A

  • Sandwich structure Janus medical dressing with asymmetric wettability and preparation method thereof

    CN118526624A